2020
DOI: 10.1371/journal.pntd.0008781
|View full text |Cite
|
Sign up to set email alerts
|

Capture-based enrichment of Theileria parva DNA enables full genome assembly of first buffalo-derived strain and reveals exceptional intra-specific genetic diversity

Abstract: Theileria parva is an economically important, intracellular, tick-transmitted parasite of cattle. A live vaccine against the parasite is effective against challenge from cattle-transmissible T. parva but not against genotypes originating from the African Cape buffalo, a major wildlife reservoir, prompting the need to characterize genome-wide variation within and between cattle- and buffalo-associated T. parva populations. Here, we describe a capture-based target enrichment approach that enables, for the first … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 103 publications
1
7
0
Order By: Relevance
“…Available data so far supports the arguments that buffalo-derived T. parva is distinct from cattle-derived strains (Oura et al, 2011;Elisa et al, 2014) with cattle strains being less diverse, subset of the buffalo strains (Oura et al, 2003;Pelle et al, 2011). A similar study done by Palmateer et al (2020), also using bait capture found buffaloderived T. parva to be highly divergent from cattle-derived T. parva. While this latter genome would be of interest to use as an alternative reference genome to the Muguga genome, it still needs refinement with regard to assignment of contigs to the correct homologous chromosomes of the Muguga genome.…”
Section: Discussionsupporting
confidence: 53%
“…Available data so far supports the arguments that buffalo-derived T. parva is distinct from cattle-derived strains (Oura et al, 2011;Elisa et al, 2014) with cattle strains being less diverse, subset of the buffalo strains (Oura et al, 2003;Pelle et al, 2011). A similar study done by Palmateer et al (2020), also using bait capture found buffaloderived T. parva to be highly divergent from cattle-derived T. parva. While this latter genome would be of interest to use as an alternative reference genome to the Muguga genome, it still needs refinement with regard to assignment of contigs to the correct homologous chromosomes of the Muguga genome.…”
Section: Discussionsupporting
confidence: 53%
“…The advent of genomic analysis has added further insight, with the initial sequencing of nine isolates indicating that the two genomes of buffalo-derived T. parva analyzed were divergent, with twice the number of single nucleotide polymorphisms (SNPs) compared to the T. parva reference genome (T. parva Muguga-originally isolated from a cow) compared to seven genomes of cattle-derived T. parva (Hayashida et al, 2013). This putative divergence has been recently supported by the first de novo genome assembly of a buffalo-derived T. parva isolate, which indicated a slightly larger genome, significantly high nonsynonymous nucleotide diversity and genome-wide F ST values compared to the T. parva Muguga genome, at levels compatible with those observed between species rather than within species (Palmateer et al, 2020).…”
Section: Introductionmentioning
confidence: 63%
“…However, the indications of separate clusters of genotypes that derive from either only buffalo or from both cattle and buffalo, alternatively suggest that this may be an example of incipient speciation, with divergence between cattle and buffalo-derived samples in process, i.e., comparable to but at an earlier stage of divergence than the very closely related T. sp. (buffalo) (Palmateer et al, 2020)-albeit that in T. sp. (buffalo) this is suggested to be due to adaptation to a different tick species rather than a different mammalian host (Bishop et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, the genetic underpinnings of these strain differences are yet to be fully unraveled, and a precise delineation of the various genotypes is lacking [ 23 ]. This is partly because of the parasite’s biology, which renders it technically unamenable for genomic studies, especially in obtaining pure parasite DNA free from host-DNA contamination [ 26 ]. An accurate determination of the origin (buffalo or cattle derived) and geographic spread of strains will help intervention and control efforts.…”
Section: Introductionmentioning
confidence: 99%